Chemical mechanical polishing composition suitable for planarization of silicon-based device and application of chemical mechanical polishing composition
By using oxidants, polyethylene glycol grafted silica sol and bipyridine in chemical mechanical polishing technology, the problem of wafer surface defects during polishing process in semiconductor manufacturing is solved, and the stability and polishing rate of the polishing liquid are improved. , improving the flatness and reliability of the device.
Patent Information
- Application Number
- CN202310843210.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
Existing chemical mechanical polishing technology can easily lead to wafer surface defects in semiconductor manufacturing, including foreign impurities, scratches, chemical and electrochemical erosion, which affects device performance and reliability, especially in the polishing process of copper wiring layer, which is difficult to control defects. Meet the requirements of advanced processes.
By using a chemical mechanical polishing composition including an oxidant, polyethylene glycol grafted silica sol, complexing agent, bipyridine and its derivatives, corrosion inhibitors and surfactants, the hydrophilicity and hardness of the silica sol , reduce frictional damage, and form a film layer by acting with metal atoms to reduce defects on the polished surface.
It effectively reduces the number of defects on the wafer surface after polishing, improves the stability and polishing rate of the polishing liquid, reduces mechanical damage and chemical corrosion during the polishing process, and improves the flatness and reliability of the device.
Smart Images

Figure BDA0004331353350000091 
Figure BDA0004331353350000092 
Figure BDA0004331353350000093
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chemical mechanical polishing, and in particular to a chemical mechanical polishing composition suitable for planarizing silicon-based devices in the field of semiconductor manufacturing and an application thereof. Background Art
[0002] The demand for smaller chip size and higher computing / storage capabilities can be achieved by reducing line width and increasing the number of metal wiring layers, which requires good flatness between chip layers. Currently, the only technology to achieve good interlayer flatness in chip manufacturing is chemical mechanical polishing (CMP).
[0003] Copper has been widely used as a wiring metal in integrated circuit manufacturing instead of aluminum, mainly due to the advantages of Cu wiring, such as lower resistivity and RC delay, better resistance to electromigration, etc. The dual Damascene process is used to make the copper wiring layer. The general steps are as follows: first, a groove is etched on the dielectric layer; then a copper barrier layer such as Ta / TaN is filled in the groove. In order to improve the adhesion between copper and the groove, a copper seed layer is deposited; finally, the electroplating method is used to fill the groove with copper; finally, the copper wiring layer is CMPed.
[0004] After CMP, wafers are prone to defects. When defects exist on the wafer surface, they will cause short circuits or open circuits, and cause device performance and reliability drift. During the CMP stage, defects have the most direct impact on yield and reliability. Post-CMP defect control indicators have become one of the most stringent indicators in the entire chip processing process.
[0005] The main defects after CMP are: 1) Foreign impurities and polishing residues: Nanoparticles in the polishing liquid and polishing debris on the polishing pad will remain on the surface of the wafer after polishing. 2) Scratches and mechanical damage: When preparing the polishing liquid, excessive local ion concentration will lead to the agglomeration of nanoparticles with electrostatic repulsion as the stabilization source. During the storage of the polishing liquid, changes in external environmental factors will aggravate the unstable state of the polishing liquid, resulting in the agglomeration of nanoparticles. These agglomerates will scratch the wafer during the polishing process. The instability of the output parameters of the polishing machine during operation will cause mechanical damage to the wafer. 3) Chemical and electrochemical corrosion: In chemical mechanical polishing, especially metal polishing, chemical reactions are the main reaction. Excessive chemical corrosion can cause defects such as pits and open circuits in the interconnection lines on the wafer surface. Electrochemical corrosion occurs during barrier layer polishing. Two metals with different corrosion potentials, such as copper-cobalt, are prone to galvanic corrosion.
[0006] Post-CMP defects can be improved by optimizing the components of the polishing liquid. Patent CN101397481A discloses a composition comprising quaternary ammonium cations, corrosion inhibitors, polymer compounds with sulfonic groups at the ends, inorganic ions and organic acids, which improves wafer scratches after polishing, but sulfonic polymers can cause foaming in the polishing liquid, which is not conducive to the performance stability of the polishing liquid. Patent CN109690741A uses silica particles with the same sign as the metal potential being polished for polishing, which reduces the number of defects on the copper and TEOS surfaces after polishing, but the removal rates of TEOS and Cu are low. Patent CN111004579A discloses a special composition of a chelating agent and a surfactant to reduce defects. Patent CN109690741A improves the defects of the polished surface by controlling the potential of the abrasive particles and the polished surface. In the polishing of the barrier layer, the defect level is a key parameter for evaluating the quality of the polished surface, and its performance is directly related to the device performance. As chip feature sizes decrease, higher requirements are placed on defect control. Therefore, it is necessary to improve the composition of the polishing liquid formula to meet the requirements of advanced processes. Summary of the invention
[0007] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a chemical mechanical polishing composition suitable for planarizing silicon-based devices in the field of semiconductor manufacturing, and the polishing composition can improve the defects of the polished surface of the silicon-based device.
[0008] Another object of the present invention is to provide the use of the chemical mechanical polishing composition suitable for planarizing silicon-based devices in the field of semiconductor manufacturing in chemical mechanical polishing.
[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0010] A chemical mechanical polishing (CMP) composition suitable for planarizing silicon-based devices comprises an oxidant, polyethylene glycol-grafted silica sol, a complexing agent, bipyridine and its derivatives, a corrosion inhibitor, a surfactant and deionized water.
[0011] In a preferred embodiment, the mass percentage of the components of the polishing composition is: 0.01wt%-5wt% of oxidant, 2-30wt% of polyethylene glycol grafted silica sol, 0.01wt%-5wt% of complexing agent, 0.01wt%-1wt% of bipyridine and its derivatives, 0.01wt%-1wt% of corrosion inhibitor, 0.001wt%-1wt% of surfactant, and the balance is deionized water.
[0012] In a specific embodiment, the silica sol is prepared by any one of a single substance silicon method, an ion exchange method, and a sol-gel method, preferably an ion exchange method; more preferably, the size of the silica sol is 10-300 nm.
[0013] In a specific embodiment, the polyethylene glycol grafted silica sol is a silica sol with polyethylene glycol grafted on the surface, and preferably the degree of polymerization of the polyethylene glycol is 200-20000; more preferably, the number of polyethylene glycol grafted on the surface of the silica sol is 0.01-1 per square nanometer.
[0014] In a specific embodiment, the complexing agent is selected from any one of citric acid, methylmalonic acid, oxalic acid, acetic acid, glycine, valine, and ethylenediaminetetraacetic acid.
[0015] In a specific embodiment, the bipyridine and its derivatives are selected from dipyridine, terpyridine and their derivatives; preferably selected from any one of 2,2'-bipyridine, 4,4'-bipyridine, 2,2'-bipyridine-5,5'-dicarboxylic acid, 2,2'-bipyridine-5,5'-dicarboxaldehyde, 4,4'-dimethyl-2,2'-bipyridine, 5,5-diamino-2,2'-bipyridine, 2,2'-bipyridine-4,4'-dicarboxylic acid, 2,4'-bipyridine, 2,3'-bipyridine, and 5,5'-dimethyl-2,2'-bipyridine, more preferably 2,2'-bipyridine or 4,4'-bipyridine.
[0016] In a specific embodiment, the corrosion inhibitor is selected from any one of aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, benzotriazole, cytosine, uracil, and 2-methyl-4-isothiazolinetrione, preferably aspartic acid, 1,2,4-triazole or 3-amino-1,2,4-triazole.
[0017] In a specific embodiment, the oxidizing agent is selected from hydrogen peroxide.
[0018] In a specific embodiment, the surfactant is a nonionic or anionic surfactant; preferably, the nonionic surfactant is selected from at least any one of polyethylene glycol, polyvinyl pyrrolidone, nonionic polyacrylamide, alkylphenol polyoxyethylene ether, polyoxyethylene alkyl alcohol, and a diblock or triblock copolymer of polyoxyethylene and polyoxypropylene; the anionic surfactant is selected from at least any one of polyacrylic acid, polyacrylic acid-polyacrylate copolymer, anionic polyacrylamide, alkylbenzene sulfonic acid, and fatty alcohol sulfate; more preferably, the molecular weight of the surfactant is 200-1000000, preferably 400-100000.
[0019] On the other hand, the chemical mechanical polishing composition is used in chemical mechanical polishing of silicon-based devices.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The silica sol used in the chemical mechanical polishing composition of the present invention is polyethylene glycol grafted silica sol, and bipyridine and its derivatives are added. The cooperation of these two substances has the following benefits: 1) improving the hydrophilicity of silica sol. The adsorption energy between silica sol and wafer surface becomes smaller, which is beneficial to the removal of particles from the wafer surface; 2) reducing the hardness of silica sol. After the hardness of silica sol is reduced, the friction damage between particles and wafer surface can be reduced; 3) improving the stability of slurry. Polyethylene glycol is grafted to the surface of silica sol, which increases the steric hindrance between particles and can improve the scratches on the wafer surface; bipyridine and its derivatives are affinity for Cu and Si atoms, can form a good spread on the polishing surface, and work together with polyethylene glycol segments to form a film layer on the surface of wafer and pad, which is beneficial to reduce the occurrence of defects. DETAILED DESCRIPTION
[0022] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.
[0023] A chemical mechanical polishing composition suitable for planarizing silicon-based devices, the chemical mechanical polishing composition comprising an oxidant, polyethylene glycol grafted silica sol, a complexing agent, bipyridine and its derivatives, a corrosion inhibitor, a surfactant and deionized water. The mass percentage of each component of the polishing composition is: 0.01wt%-5wt% of the oxidant, 2-30wt% of the polyethylene glycol grafted silica sol, 0.01wt%-5wt% of the complexing agent, 0.01wt%-1wt% of bipyridine and its derivatives, 0.01wt%-1wt% of the corrosion inhibitor, 0.001wt%-1wt% of the surfactant, and the balance is deionized water.
[0024] In actual use, other additives may be added as needed, for example, 0.001 wt% to 0.1 wt% of a fungicide.
[0025] Wherein, as the silica sol, it is prepared by any one of the methods of elemental silicon method, ion exchange method and sol-gel method, and the preferred preparation method is ion exchange method. There is no restriction on its preparation method, and the specific preparation method can refer to the prior art, or the corresponding abrasive can be directly purchased on the market. In addition, the size of the grinding particles is 10-300nm, including but not limited to 10nm, 20nm, 50nm, 75nm, 100nm, 120nm, 150nm, 180nm, 200nm, 230nm, 250nm, 270nm, 285nm, 300nm, preferably 50-150nm. In addition, the surface of the silica sol is grafted with polyethylene glycol, and the degree of polymerization of the polyethylene glycol grafted on the surface is preferably 200-20000, including but not limited to 200, 500, 1000, 2000, 5000, 10000, 12000, 15000, 20000. The number of polyethylene glycol grafted on the surface of the silica sol is 0.01-1 per square nanometer, including but not limited to 0.01, 0.1, 0.5, 0.8, and 1. Within the range of the degree of polymerization of polyethylene glycol and the number of grafted, the stability of the silica sol will be relatively better and the removal rate will be relatively lower.
[0026] Polyethylene glycol grafted silica sol, also known as polyethylene glycol modified silica sol or polyethylene glycol modified silica sol, has no particular limitation on its preparation method, and can adopt the preparation method of the prior art, such as the preparation method of reference "10.1016 / j.colsurfa.2009.08.008", which specifically includes the following steps: 1) dissolving polyethylene glycol dimethyl ether (PEGME) in tetrahydrofuran (TFT). Add isocyanate propyl triethoxysilane (IPTES) and dibutyltin dilaurate (DBDU) to the solution, and stir at 80°C for 8 hours under a nitrogen atmosphere. After the reaction is completed, the tetrahydrofuran is evaporated using a rotary evaporator to obtain PEGME-IPTES. 2) Grafting PEGME-IPTES to silica sol, the reaction is similar to the modification of silica sol by a silane coupling agent. In an alkaline environment, PEGME-IPTES was added to silica sol and stirred at 80°C for 2 hours to obtain polyethylene glycol-modified silica sol.
[0027] Of course, the polyethylene glycol-grafted silica sol of the present invention can also be purchased directly from the market, for example, from Creative PEGworks.
[0028] The polyethylene glycol grafted silica sol is added in an amount of 2-30wt% of the mass of the polishing composition, for example including but not limited to 2wt%, 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 20wt%, 25wt%, 30wt%.
[0029] The complexing agent is selected from any one of citric acid, methylmalonic acid, oxalic acid, acetic acid, glycine, valine, and ethylenediaminetetraacetic acid, preferably glycine and acetic acid. The amount of the complexing agent added is 0.01wt%-5wt% of the mass of the polishing composition, for example, including but not limited to 0.01wt%, 0.1wt%, 0.2wt%, 0.4wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 5wt%. The addition of the complexing agent in the polishing composition is conducive to complexing free metal ions in the polishing liquid and promoting the removal of copper. Adding too much will lead to an increase in the roughness of the polishing surface, adding too little will not achieve the required copper removal rate, and copper compound residues are easily generated on the surface of the polishing pad after polishing.
[0030] The bipyridine and its derivatives are selected from dipyridine or terpyridine and their derivatives, preferably any one of 2,2'-bipyridine, 4,4'-bipyridine, 2,2'-bipyridine-5,5'-dicarboxylic acid, 2,2'-bipyridine-5,5'-dicarboxaldehyde, 4,4'-dimethyl-2,2'-bipyridine, 5,5-diamino-2,2'-bipyridine, 2,2'-bipyridine-4,4'-dicarboxylic acid, 2,4'-bipyridine, 2,3'-bipyridine, and 5,5'-dimethyl-2,2'-bipyridine, and more preferably 2,2'-bipyridine and 4,4'-bipyridine.
[0031] The amount of bipyridine and its derivatives added is 0.01wt%-1wt% of the mass of the polishing composition, for example, including but not limited to 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.4wt%, 0.8wt%, 1wt%. The addition of bipyridine and its derivatives in the polishing composition can act on both the metal surface and silicon to reduce the defects of the polished surface.
[0032] The corrosion inhibitor is any one selected from aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, benzotriazole, cytosine, uracil, and 2-methyl-4-isothiazolinetrione, preferably aspartic acid, 1,2,4-triazole or 3-amino-1,2,4-triazole.
[0033] The corrosion inhibitor is added in an amount of 0.01wt%-1wt% of the mass of the polishing composition, including but not limited to 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%. The addition of the corrosion inhibitor to the polishing composition can form a protective film with the metal surface, inhibit static corrosion of the metal, and regulate the removal rate of the metal.
[0034] As the surfactant, nonionic and anionic surfactants are selected. As an example of nonionic surfactant, at least one of polyethylene glycol, polyvinyl pyrrolidone, nonionic polyacrylamide, alkylphenol polyoxyethylene ether, polyoxyethylene alkyl alcohol, diblock or triblock copolymers of polyoxyethylene and polyoxypropylene is preferably selected. As an example of anionic surfactant, at least one of polyacrylic acid, polyacrylic acid-polyacrylate copolymer (also called acrylic acid-acrylate copolymer), anionic polyacrylamide, alkylbenzene sulfonic acid, and fatty alcohol sulfate is preferably selected. Preferably, the molecular weight of the surfactant is 200-1000000, such as 200, 500, 1000, 5000, 10000, 50000, 60000, 80000, 100000, 150000, 500000, 800000, 1000000, etc., preferably 400-100000.
[0035] The surfactant is added in an amount of 0.001wt%-1wt% of the polishing composition, including but not limited to 0.001wt%, 0.005wt%, 0.01wt%, 0.1wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%. Too little surfactant will not achieve the desired effect, while too much surfactant will reduce the material removal rate.
[0036] The oxidant is hydrogen peroxide. Hydrogen peroxide first oxidizes the metal into an oxidized state to form a softened oxide film, which is removed by mechanical action and the complexing action of the complexing agent. The amount of the oxidant added is 0.01wt%-5wt% of the mass of the polishing composition, for example, including but not limited to 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%. If too little hydrogen peroxide is added, not only the required metal removal rate cannot be achieved, but also the surface roughness of the metal after polishing is high, and too much addition will inhibit the metal removal rate.
[0037] The present invention is further explained below by more specific examples, but does not constitute any limitation.
[0038] Polyethylene glycol grafted silica sol was purchased from Creative PEGworks.
[0039] Other reagents, instruments and materials used in the examples and comparative examples of the present invention were purchased from commercial sources.
[0040] Table 1 Silica sol information used in the present invention
[0041]
[0042] Polishing liquid preparation
[0043]
[0044] Mix the substances in the table evenly and make up the balance in the formula with deionized water. See Table 2 for the specific ingredients.
[0045] After the above substances are mixed evenly, 0.5 wt % of hydrogen peroxide is added thereto and mixed evenly to obtain a sample for polishing. In order to reduce the experimental error caused by the decomposition of hydrogen peroxide over time, the sample is used within 3 hours after the preparation is completed.
[0046] Table 2 Chemical mechanical polishing liquid composition table of comparative examples and embodiments
[0047]
[0048]
[0049]
[0050] Polishing rate evaluation
[0051] In the following embodiments, the instruments and parameters used in the polishing of the copper dielectric and dielectric layer TEOS are as follows:
[0052]
[0053] In the following embodiments, the copper wafer used for polishing is a 1000A copper film electroplated on a 600 micron (100) crystal plane single crystal silicon substrate, and the copper wafer size is 12 inches. The TEOS wafer used for polishing is a 10000A TEOS film prepared on a 600 micron (100) crystal plane single crystal silicon substrate by physical vapor deposition. The above metal and non-metal film layer materials can be obtained from the market.
[0054] On the diameter of a 12-inch wafer, take the zero point as the starting point, select a point every 1 cm in the positive and negative directions, and take a total of 28 points. Use a four-probe conductivity meter to test the conductivity of the points in the selected area on the copper wafer, so as to calculate the thickness of the copper wafer. The difference in thickness of the copper wafer before and after polishing divided by the polishing time is the polishing rate.
[0055] Surface defect detection
[0056] Use a surface defect detector to measure the number of surface defects. Use the ratio of the number of wafer surface defects after polishing to the number of wafer surface defects before polishing to define the change in surface defects after polishing. The smaller the ratio, the more defects have been repaired.
[0057] Defect measurement range of Cu and TEOS surface: 200nm-808nm.
[0058] The polishing liquid prepared in the embodiment and comparative example was used for chemical mechanical polishing of copper-plated wafers on a single crystal silicon substrate according to the aforementioned method to evaluate the polishing rate and surface defects. The relevant evaluation results are shown in Table 3.
[0059] Table 3 Polishing rate, rate selection ratio, and ratio of the number of defects before and after polishing
[0060]
[0061] As can be seen from the above table, compared with Example 1, the ratio of the number of defects after polishing to the number of defects before polishing of the TEOS and Cu surfaces of Example 1 using polyethylene glycol grafted silica sol and 2,2'-bipyridine is significantly reduced. Compared with Example 2, the ratio of the number of defects after polishing to the number of defects before polishing of the TEOS and Cu surfaces of Example 1 using polyethylene glycol grafted silica sol and 2,2'-bipyridine is smaller than that of the comparative example 2 in which 2,2'-bipyridine is added to the formula but there is no polyethylene glycol grafted silica sol. Compared with Example 1, the reduction of defects after polishing of the TEOS and Cu of the comparative example 3 using only polyethylene glycol grafted silica sol is higher than that of Example 1. The above shows that polyethylene glycol grafted silica sol and 2,2'-bipyridine can have a significant effect on reducing defects.
[0062] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A chemical mechanical polishing composition suitable for planarizing silicon-based devices, characterized in that: The invention comprises an oxidant, polyethylene glycol grafted silica sol, a complexing agent, bipyridine and its derivatives, a corrosion inhibitor, a surfactant and deionized water.
2. The chemical mechanical polishing composition according to claim 1, wherein The mass percentage of each component in the chemical mechanical polishing composition is: 0.01wt%-5wt% of an oxidant, 2-30wt% of polyethylene glycol grafted silica sol, 0.01wt%-5wt% of a complexing agent, 0.01wt%-1wt% of bipyridine and its derivatives, 0.01wt%-1wt% of a corrosion inhibitor, 0.001wt%-1wt% of a surfactant, and the balance is deionized water.
3. The chemical mechanical polishing composition according to claim 1 or 2, characterized in that The silica sol is prepared by any one of a single substance silicon method, an ion exchange method, and a sol-gel method, preferably the ion exchange method; more preferably, the size of the silica sol is 10-300 nm.
4. The chemical mechanical polishing composition according to claim 1 or 2, characterized in that The polyethylene glycol grafted silica sol is a silica sol with polyethylene glycol grafted on the surface, and preferably the degree of polymerization of the polyethylene glycol is 200-20000; more preferably, the number of polyethylene glycol grafted on the surface of the silica sol is 0.01-1 per square nanometer.
5. The chemical mechanical polishing composition according to claim 1 or 2, characterized in that: The complexing agent is selected from any one of citric acid, methylmalonic acid, oxalic acid, acetic acid, glycine, valine, and ethylenediaminetetraacetic acid.
6. The chemical mechanical polishing composition according to claim 1 or 2, characterized in that: The bipyridine and its derivatives are selected from dipyridine, terpyridine and their derivatives; preferably selected from any one of 2,2'-bipyridine, 4,4'-bipyridine, 2,2'-bipyridine-5,5'-dicarboxylic acid, 2,2'-bipyridine-5,5'-dicarboxaldehyde, 4,4'-dimethyl-2,2'-bipyridine, 5,5-diamino-2,2'-bipyridine, 2,2'-bipyridine-4,4'-dicarboxylic acid, 2,4'-bipyridine, 2,3'-bipyridine, and 5,5'-dimethyl-2,2'-bipyridine, more preferably 2,2'-bipyridine or 4,4'-bipyridine.
7. The chemical mechanical polishing composition according to claim 1 or 2, characterized in that: The corrosion inhibitor is selected from any one of aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, benzotriazole, cytosine, uracil, and 2-methyl-4-isothiazolinetrione, preferably aspartic acid, 1,2,4-triazole or 3-amino-1,2,4-triazole.
8. The chemical mechanical polishing composition according to claim 1 or 2, characterized in that: The oxidizing agent is selected from hydrogen peroxide.
9. The chemical mechanical polishing composition according to claim 1 or 2, characterized in that The surfactant is a nonionic or anionic surfactant; preferably, the nonionic surfactant is selected from at least any one of polyethylene glycol, polyvinyl pyrrolidone, nonionic polyacrylamide, alkylphenol polyoxyethylene ether, polyoxyethylene alkyl alcohol, and a diblock or triblock copolymer of polyoxyethylene and polyoxypropylene; the anionic surfactant is selected from at least any one of polyacrylic acid, polyacrylic acid-polyacrylate copolymer, anionic polyacrylamide, alkylbenzene sulfonic acid, and fatty alcohol sulfate; more preferably, the molecular weight of the surfactant is 200-1000000, preferably 400-100000.
10. Use of the chemical mechanical polishing composition according to any one of claims 1 to 9 in chemical mechanical polishing of silicon-based devices.
Citation Information
Patent Citations
Polishing liquid
CN101397481A
CMP polishing solution and polishing method
CN109690741A
Alkaline polishing solution for reducing CMP defects of multi-layer copper interconnection barrier layer and preparation method of alkaline polishing solution
CN111004579A